Mycoplasma genitalium: An Emerging Cause of Pelvic Inflammatory Disease - Catherine L. Haggerty; Brandie D. Taylor (Hindawi Limited, 2011)
Mycoplasma genitalium is a sexually transmitted pathogen that is increasingly identified among women with pelvic inflammatory disease (PID). Although Chlamydia trachomatis and Neisseria gonorrhoeae frequently cause PID, up to 70% of cases have an unidentified etiology. This paper summarizes evidence linking M. genitalium to PID and its long-term reproductive sequelae. Several PCR studies have demonstrated that M. genitalium is associated with PID, independent of gonococcal and chlamydial infection. Most have been cross-sectional, although one prospective investigation suggested that M. genitalium was associated with over a thirteenfold risk of endometritis. Further, a nested case-control posttermination study demonstrated a sixfold increased risk of PID among M. genitalium positive patients. Whether or not M. genitalium upper genital tract infection results in long-term reproductive morbidity is unclear, although tubal factor infertility patients have been found to have elevated M. genitalium antibodies. Several lines of evidence suggest that M. genitalium is likely resistant to many frequently used PID treatment regimens. Correspondingly, M. genitalium has been associated with treatment failure following cefoxitin and doxycycline treatment for clinically suspected PID. Collectively, strong evidence suggests that M. genitalium is associated with PID. Further study of M. genitalium upper genital tract infection diagnosis, treatment and long-term sequelae is warranted.